“Without Me” by Egor Letov: Text and Context - AFANASEV, ANTON SERGEEVICH; NIKOLAEVNA BREEVA, TATYANA; DOMANSKY, JURY VIKTOROVICH; VINNIKOVA, MARINA NIKOLAEVNA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT According to the collection of poems, in the poetry of Igor Fedorovich Letov, there was a four-year period (from 1998 to 2001), when not a single poetic text was created. And it was the composition “Without Me” (2002), which became the first written work after a long break and later a part of the album of "Grazhdanskaya oborona" (civil defence) "Dolgaya schastlivaya zhizn’" (long happy life) (2004). It was found that this composition fits into the context of Yegor Letov’s entire work. The team of authors considers the so-called “texts of death” in which the theme of death is central. RESUMEN Según la colección de poemas, en la poesía de Igor Fedorovich Letov hubo un período de cuatro años (de 1998 a 2001), cuando no se creó un solo texto poético. Y fue la composición "Sin mí" (2002), que se convirtió en la primera obra escrita después de un largo descanso, y posteriormente una parte del álbum de "Grazhdanskaya oborona" (defensa civil) "Dolgaya schastlivaya zhizn ’" (larga vida feliz) (2004). Se descubrió que esta composición encaja en el contexto de toda la obra de Yegor Letov. El equipo de autores considera los llamados "textos de muerte" en los cuales el tema de la muerte es central.